Enhancing Employability for Autistic Graduates: Using TRIZ Theory to Design Virtual Reality Solutions for Fostering Inclusive Communications in Workplace Environments (Global Journal of Human-Social Science, 2023)
The underemployment of post-secondary graduates with autism AP-PSD is a critical concern This issue often stems from difficulties in workplace integration and communication This research explores the potential of virtual reality VR systems to alleviate these challenges by simulating work environments The methodology rooted in the TRIZ Theory a problem-solving algorithm refines the use of VR systems for enhanced adaptability and efficiency The primary objectives include enhancing employers understanding of AP-PSD-related issues and identifying significant workplace challenges faced by AP-PSDs Through literature reviews surveys and focus groups the study investigates the factors impacting AP-PSDs and identifies key components to develop a more effective VR system to support their workplace integration The research also scrutinizes existing technological adaptations that could improve situation recognition communication and understanding in the workplace Additionally the potential role of human supervision in conjunction with VR technology support for AP-PSD employees is considered The results suggest that regardless of company size supporting AP-PSDs in the workplace is a feasible goal that can enhance their wellbeing Crucially the AP-PSD s active participation in their own integration process which encompasses training human support and environmental adaptations along with the specific involvement of the human resources manager has proven vital With the right accommodations AP-PSDs can demonstrate up to 30 greater productivity than neurotypical employees offsetting accommodation costs This research emphasizes the need to blend human-centered approaches with technological innovations to boost AP-PSDs employability Though industry-specific integration details are beyond the scope of this study the results underline the potential for tailored solutions aligned with each company s unique culture The paper presents a prototype for further co-design phases
Keywords: autism employment; virtual reality (VR); workplace integration; emotion recognition; technological adaptations